On 10-year experience in the use of direct and antireflux techniques of anastomosis of ureter and orthotopic intestinal neobladder after radical cystectomy - Aleksić Predrag; Bančević Vladimir; Stijelja Borislav; Milović Novak; Toševski Perica; Čampara Zoran; Košević Branko; Mocović Dejan (Vojnosanitetski Pregled)
Background/Aim. Today, radical cystectomy is the method of choice in treatment of muscle invasive bladder carcinoma in stage T2-T4a, No-Nx, Mo, and orthotopic derivation is for patients the most comfortable derivation of urin. From 1888 when Tizzoni and Foggi performed the first orthotopic derivation on animals, and 1913 when Lemoin declared the first orthotopic derivation in humans there has been a constant improvement and modification of orthotopic urinary diversion after radical cystectomy which significantly decrease the number and severity of postoperative complications. The aim of this study was to compare complications regarding the direct and antireflux ureter-neobladder anastomosis. Methods. This retrospective study included 79 selected patients operated over the last ten years having medical records available. Previously, we excluded the patients with prior radiation therapy, systemic illness, diabetes mellitus, previous history of calculosis and metabolic disorders etc. Hautmann orthotopic technique was used in almost 70% of the patients. We analyzed complications regarding direct and antireflux ureter-neobladder anastomosis with a median follow-up period of 4,72 years. We followed-up the appearance of unilateral and bilateral hydronephrosis, forming of renal stones in the patients without previous history of renal calculosis, and renal insuficiency caused by stenosis on the site of anastomosis. We used the Kolmogorov-Smirnov test, Mann-Whitney U test, Student's t test i χ² test for statistic analysis. Results. The median age of the patients was 68,2 years. Totally 88.61% of the patients were male and 11.39% were female. The direct anastomotic technique secundum Wallace was used in 43.03% of the operated patients and antireflux technique secundum Le Duc in 56.97%. Renal deterioration caused by stenosis on the site of the ureter-neobladder anastomosis was statistically significantly higher in the antireflux anastomosis compared to direct anastomosis (χ²= 4.71, p = 0.0299). No one of the patients with direct anastomosis had poucho-ureteral reflux higher grade than gr III. Conclusion. In our study, complication as renal deterioration as a result of stenosis on the site of the ureter anastomosis was significantly more common in the group of patients exposed to antireflux technique.